Transformative social innovation and (dis)empowerment - Avelino, Flor; Wittmayer, Julia M.; Pel, Bonno; Weaver, Paul; Dumitru, Adina; Haxeltine, Alex; Kemp, René; Jørgensen, Michael S.; Bauler, Tom; Ruijsink, Saskia; O'Riordan, Tim (Technological Forecasting and Social Change, 2019)
This article responds to increasing public and academic discourses on social innovation, which often rest on the assumption that social innovation can drive societal change and empower actors to deal with societal challenges and a retreating welfare state. In order to scrutinise this assumption, this article proposes a set of concepts to study the dynamics of transformative social innovation and underlying processes of multi-actor (dis)empowerment. First, the concept of transformative social innovation is unpacked by proposing four foundational concepts to help distinguish between different pertinent 'shades' of change and innovation: 1) social innovation, (2) system innovation, (3) game-changers, and (4) narratives of change. These concepts, invoking insights from transitions studies and social innovations literature, are used to construct a conceptual account of how transformative social innovation emerges as a co-evolutionary interaction between diverse shades of change and innovation. Second, the paper critically discusses the dialectic nature of multi-actor (dis)empowerment that underlies such processes of change and innovation. The paper then demonstrates how the conceptualisations are applied to three empirical case-studies of transformative social innovation: Impact Hub, Time Banks and Credit Unions. In the conclusion we synthesise how the concepts and the empirical examples help to understand contemporary shifts in societal power relations and the changing role of the welfare state.
Num Pages: 195 Place: New York, United Kingdom Publisher: Elsevier Science Ltd.
Keywords: Définition; Empowerment; Innovation sociale transformatrice; Réservé UdeM; Université

Transformative social innovation and (dis)empowerment - Avelino, Flor; Wittmayer, Julia M.; Pel, Bonno; Weaver, Paul; Dumitru, Adina; Haxeltine, Alex; Kemp, René; Jørgensen, Michael S.; Bauler, Tom; Ruijsink, Saskia; O'Riordan, Tim (Technological Forecasting and Social Change, 2019)
This article responds to increasing public and academic discourses on social innovation, which often rest on the assumption that social innovation can drive societal change and empower actors to deal with societal challenges and a retreating welfare state. In order to scrutinise this assumption, this article proposes a set of concepts to study the dynamics of transformative social innovation and underlying processes of multi-actor (dis)empowerment. First, the concept of transformative social innovation is unpacked by proposing four foundational concepts to help distinguish between different pertinent 'shades' of change and innovation: 1) social innovation, (2) system innovation, (3) game-changers, and (4) narratives of change. These concepts, invoking insights from transitions studies and social innovations literature, are used to construct a conceptual account of how transformative social innovation emerges as a co-evolutionary interaction between diverse shades of change and innovation. Second, the paper critically discusses the dialectic nature of multi-actor (dis)empowerment that underlies such processes of change and innovation. The paper then demonstrates how the conceptualisations are applied to three empirical case-studies of transformative social innovation: Impact Hub, Time Banks and Credit Unions. In the conclusion we synthesise how the concepts and the empirical examples help to understand contemporary shifts in societal power relations and the changing role of the welfare state.
Num Pages: 195 Place: New York, United Kingdom Publisher: Elsevier Science Ltd.
Keywords: Définition; Empowerment; Innovation sociale transformatrice; Réservé UdeM; Université